EFEKTIFITAS BIMBINGAN KELOMPOK DENGAN TEKNIK REFRAMING UNTUK MENINGKATKAN KEPEKAAN SOSIAL SISWA KELAS XI SMAIT AL- GHAZALI JEMBER - Bil Qisthi, Qoimah; Hikmatul Maghfiroh, Nasruliyah; Ulwiyah, Imaratul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to investigate the effectiveness of group guidance using the reframing technique to enhance social sensitivity among eleventh-grade students at SMAIT Al Ghazali. The method employed is a pre-experimental design with a one-group pre-test and post-test framework. The population consisted of 23 eleventh-grade students, with a sample size of 6 students. Data analysis was conducted using the Wilcoxon test to compare pre-test and post-test scores. The results showed that the average pre-test score increased from 55 to 95.33 in the final post-test. The Wilcoxon test yielded an Asymp. Sig (2-tailed) value of 0.028, which is less than 0.05, indicating that the hypothesis is accepted. In conclusion, group guidance using the reframing technique effectively increases the social sensitivity of eleventh-grade students at SMAIT Al Ghazali in Jember.